Effective Speaking Skills and Coping Attitudes of Pediatric Nurses - Şimşek, Didem Coşkun; Günay, Ulviye (My University, 2023)
Aim: This descriptive and cross-sectional study was carried out to analyse the effective speaking skills and coping attitudes of pediatric nurses. Materials and Methods: The population of the study consists of 251 nurses working in pediatric clinics of two hospitals in the eastern region of Turkey. The data in the study were collected with Descriptive Information Form, Effective Speech Skills Scale and Coping Attitudes Assessment Scale. Results: It was found that pediatric nurses had a mean effective speech scale total score of 50.96 ±16.92 and a mean coping scale total score of 157.75±26.69. Positive significant association was found between mean effective speech scale sub-dimension scores and total scores and between mean coping attitude scale sub-dimension scores and total scores. Conclusions: It was found that descriptive characteristics of pediatric nurses such as age, years of working as a nurse and weekly working hours were effective on their effective speech skills and coping attitudes. Effective speech skills of pediatric nurses were moderate. It was found that nurses used their coping attitudes effectively as their effective speech skills developed.
Keywords: Coping attitudes; Pediatric nurse; Effective speech skills